Code Mixing Between Indonesian and English in The Website “Female Daily Review” - Fitria, Tira Nur (SALIENCE: English Language, Literature, and Education Journal, 2024)
This research describes the code-mixing found in the website “Female Daily Review”. This research is qualitative descriptive. The analysis shows that code-mixing is a phenomenon where two or more languages are used in one sentence or discourse without changing the grammatical structure of each language. In the beauty and makeup industry, many English-derived terms and phrases are commonly used, both among professionals and consumers. Female Daily Review uses various language types to convey reviews, tips, and discussions about beauty. Formal language is used for objective and informative product reviews, while informal language is used for relaxed and personal reviews. Technical language is used for discussing beauty products, while emotional language expresses excitement, disappointment, or personal experiences. Praise or criticism language is used for positive or negative reviews, while instructional language provides tips or guidance on product use, skincare, or makeup looks. Female Daily users often mix languages or code-mixing in their reviews due to their preference for English terms or the globalization of the industry. This allows users to convey their experiences with beauty products more accurately and precisely. Code mixing in product reviews on Female Daily is a common phenomenon due to factors such as a multilingual audience, global audience, culture, speaking style, influence of social media and globalization, expression of identity, vocabulary limitations, perceived quality or excellence, and connected online community. Users may create unique sentences or phrases by combining Indonesian and English words to make their reviews more interesting or different.